Spatial regulation of alpha-galactosidase activity and its influence on raffinose family oligosaccharides during seed maturation and germination in Cicer arietinum. (2nd August 2020) - Arunraj, Rex; Skori, Logan; Kumar, Abhinandan; Hickerson, Neil M.N.; Shoma, Naskar; M., Vairamani; Samuel, Marcus A.
ABSTRACT: Alpha-galactosides or Raffinose Family Oligosaccharides (RFOs) are enriched in legumes and are considered as anti-nutritional factors responsible for inducing flatulence. Due to a lack of alpha-galactosidases in the stomachs of humans and other monogastric animals, these RFOs are not metabolized and are passed to the intestines to be processed by gut bacteria leading to distressing flatulence. In plants, alpha(α)-galactosides are involved in desiccation tolerance during seed maturation and act as a source of stored energy utilized by germinating seeds. The hydrolytic enzyme alpha-galactosidase (α-GAL) can break down RFOs into sucrose and galactose releasing the monosaccharide α-galactose back into the system. Through characterization of RFOs, sucrose, reducing sugars, and α-GAL activity in maturing and germinating chickpeas, we show that stored RFOs are likely required to maintain a steady-state level of reducing sugars. These reducing sugars can then be readily converted to generate energy required for the high energy-demanding germination process. Our observations indicate that RFO levels are lowest in imbibed seeds and rapidly increase post-imbibition. Both RFOs and the α-GAL activity are possibly required to maintain a steady-state level of the reducing monosaccharide sugars, starting from dry seeds all the way through post-germination, to provide the energy for increased germination vigor.